Dimensi Brand Loyalty Bali sebagai Destinasi Wisata bagi Wisatawan Nusantara pada Masa Pandemi Covid-19 - I Made Bayu Wisnawa (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
Brand loyalty is a long-term strategy to gain a competitive advantage in tourist destinations during the Covid-19 Pandemic era, which demands more efforts for destination managers to survive. On the other hand, the dimensions used to measure brand loyalty cannot yet be agreed upon because of the complexity and diversity of perceptions. The purpose of this study was to determine: (i) the dimensions of Bali brand loyalty as a tourist destination; (ii) the efforts made to develop tourism in Bali during the Covid-19 Pandemic. This research uses a quantitative approach supported by qualitative. To test the construct of brand loyalty, the confirmatory factor analysis (CFA) technique was used with the AMOS program version 24. There were 120 respondents with the criteria that they had visited a tourist attraction in Bali at least twice. The results showed that: (i) the construct of brand loyalty is supported by cognitive, affective, conative and behavioural dimensions, where the dimension of behaviour plays a dominant role; (ii) efforts can be made by disciplined application of health protocols and promotion through social media.